Divide 2x^2 +9x - 2 by x+ 5
Answers
Answered by
6
g(x)= x+5=0
x= -5
now p(-5) = 2(-5×-5) +9(-5)-2
2(25) -45 -2
50-47
3
x= -5
now p(-5) = 2(-5×-5) +9(-5)-2
2(25) -45 -2
50-47
3
Answered by
12
Heya!!
------------------------
According to remainder theorem,
If a polynomial p(x) divided by (x- a) then remainder is equal to p(a).
Let a polynomial 2x^2 + 9x - 2 be p(x).
If it divided by (x +5) or {x - (-5)} , then remainder is equal to p(-5).
=) p(-5) = 2(-5)^2 + 9(-5) - 2
= 2(25) - 45 - 2
= 50 - 47
= 3
-------------------------
Hope it's helps u.
------------------------
According to remainder theorem,
If a polynomial p(x) divided by (x- a) then remainder is equal to p(a).
Let a polynomial 2x^2 + 9x - 2 be p(x).
If it divided by (x +5) or {x - (-5)} , then remainder is equal to p(-5).
=) p(-5) = 2(-5)^2 + 9(-5) - 2
= 2(25) - 45 - 2
= 50 - 47
= 3
-------------------------
Hope it's helps u.
Similar questions
Social Sciences,
9 months ago
Math,
9 months ago
English,
9 months ago
Math,
1 year ago
Physics,
1 year ago
Environmental Sciences,
1 year ago
English,
1 year ago